Writing Chiwere: Orthography, literacy, and language revitalization. (July 2018) - Schwartz, Saul
Abstract: Like other Native American communities left without fluent speakers of their indigenous languages, Ioways and Otoe-Missourias now rely on texts to learn Chiwere, their heritage language. This epistemological shift from speakers to texts has increased pedagogical pressures on orthographies since literacy has become the primary means of heritage language socialization and revitalization. Comparing language learning materials in use today to nineteenth-century missionary primers reveals that Chiwere orthographies and literacy have long been used to promote enculturation. While missionaries employed Chiwere literacy in their effort to convert and "civilize" Ioways and Otoe-Missourias, current language revitalization resources seek to socialize language learners to a nostalgic notion of "traditional" culture rooted in recursive entextualizations and recontextualizations of elders' words. Highlights: Ioway and Otoe-Missouria tribal members now rely on texts to learn Chiwere. Literacy has become the primary means of language socialization and revitalization. Chiwere orthographies and literacy are implicated in projects of enculturation. Missionaries used literacy as a means "civilizing" Chiwere speakers. Chiwere language revitalization promotes nostalgic notions of traditional culture.